Re-dynamising Local Economies in the Age of Trumpism - Bauwens, Michel; Niaros, Vasilis (Journal of Futures Studies, 2017)
The article presents the authors' arguments on the political and policy response behind the rise of Trumpism according from the analysis of authors Kojin Karatani, Karl Polanyi and Mark Blyth. Topics discussed include Karatani's book "The Structure of World History" on the integration of modalities for political and economic system, Polanyi's analysis in the book "The Great Transformation" on the systemic balance and the transition in regimes of value for re-alignment of modalities.
Keywords: BLYTH, Mark; Futures studies; Great Transformation, The (Book); KARATANI, Kojin; Structure of World History: From Modes of Production to Modes of Exchange, The (Book); TRUMP, Donald; Trumpism; disembeddedness; local economies; technology

The Market and Falling Fertility: Why Darwin Needs Help From Polanyi - Yea, Sanghan (World Futures: The Journal of General Evolution, 2011)
Darwin said all living things tend to multiply. However, nowadays, maintaining fertility rate below the replacement level of 2.1, human beings appear to have opted to let their population shrink. Perplexingly, it occurs while the environment seems to become more suitable for their survival. In solving this puzzle, we get a great help from Polanyi. We proved that people choose to have fewer babies and consequently, usher in depopulation, because by giving them the chance to assess all the expenses necessary for raising children, the market makes the cost clarified increasingly, while the economic benefit from rearing their off-spring remains obscure.
Keywords: DARWIN, Charles, 1809-1882; and memes; below replacement-level fertility; cultural transmission; demographic change; depopulation; exchange; futures research; general evolution; human fertility; markets; memes; reciprocity; redistribution

Why Karl Polanyi Still Matters - Bollier, David (On the Commons, 2009)
It's a ripe moment to dust off "The Great Transformation" and its anthropological critique of "self-regulating markets."
Keywords: commons

The Commons as a New Sector of Value-Creation - Bollier, David (Kosmos, 2008)
Let me start with a bit of wisdom I once picked up from Thomas Berry, a historian of cultures who has said, “The universe is the communion of subjects, not a collection of objects.” This epigraph encapsulates the monumental shift that I believe we are undergoing as we move into a new kind of cultural if not economic reality. This article was originally published in the Fall | Winter 2008 issue of Kosmos Journal. To download a PDF version of this article, please click here.
Keywords: commons

The Political Economy of Revolution: Karl Polanyi in Tahrir Square - Zayed, Hany (Theory, Culture & Society, 2022)
The causes and consequences of revolutionary change have long been the subject of scholarly debate. Through a systematic integration of political economic elements into an analysis of contemporary social transformations, this article joins this conversation by asking how Karl Polanyi’s double movement framework can clarify, and be extended by, the Egyptian Revolution of 2011. By embedding a nuanced account of neoliberalism in Egypt’s modern politics and by bringing those in dialogue with Polanyi’s theoretical apparatus, this article contends that there is a broad alignment between the first movement and the Egyptian neoliberal experience, a partial alignment between the second movement and the Egyptian Revolution, and a multilayered entanglement that implicates and encircles both movements. Not only does this research demonstrate that contemporary Egyptian history can find new currency in and be further illuminated by Polanyi’s political economy, it also critiques, complicates, reconceptualizes and extends Polanyi’s theoretical framework. In so doing, it redresses the underfocus of Polanyian political economy on the theory of revolution in general and the Egyptian Revolution in particular, problematizes extant accounts on neoliberalism and the double movement, and extends analyses between neoliberalism and revolution in political economy literatures. By clarifying our understanding of contemporary social change, this essay underscores how Polanyi’s work remains a pertinent, viable and valuable prism to examine momentous social transformations.
Keywords: Egypt; Karl Polanyi; double movement; neoliberalism; revolution

Ecology, Democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Ryan, J. Michael (COVID-19: Volume I: Global Pandemic, Societal Responses, Ideological Solutions, 2020)
The SARS-CoV-2 virus, and the associated COVID-19 pandemic, is perhaps the greatest threat to life, and lifestyles, the world has known in more than a century. The scholarship included here provides critical insights into the ethics and ideologies, inequalities, and changed social understandings that lie at the heart of this pandemic. This volume maps out the ways in which the pandemic has impacted (most often disproportionately) societies, the successes and failures of means used to combat the virus, and the considerations and future possibilities – both positive and negative – that lie ahead. While the pandemic has brought humanity together in some noteworthy ways, it has also laid bare many of the systemic inequalities that lie at the foundation of our global society. This volume is a significant step toward better understanding these impacts. The work presented here represents a remarkable diversity and quality of impassioned scholarship and is a timely and critical advance in knowledge related to the pandemic. This volume and its companion, COVID-19: Volume II: Social Consequences and Cultural Adaptations, are the result of the collaboration of more than 50 of the leading social scientists from across five continents. The breadth and depth of the scholarship is matched only by the intellectual and global scope of the contributors themselves. The insights presented here have much to offer not just to an understanding of the ongoing world of COVID-19, but also to helping us (re-) build, and better shape, the world beyond.
Keywords: COVID-19; disease & health Issues; health

Introduction : exploring markets - Peck, Jamie; Berndt, Christian; Rantisi, Norma (Market/Place: Exploring Spaces of Exchange, 2020)
The origin of the present volume was an invitational workshop focused on questions of the spatiality and diversity of markets, held at the Karl Polanyi Institute of Political Economy in Montreal in the summer of 2017. This was an apt meeting place in a more than literal sense. Although many of those in attendance did not subscribe explicitly to a Polanyian worldview or mode of analysis, most had engaged with Polanyi’s work in different ways. Some had made extensive contributions to neo-Polanyian scholarship, while others were more closely affiliated to radical political economy, performativity approaches or poststructuralism. In this context, more pertinent were a series of broadly aligned sympathies with what might be characterized as Polanyian dispositions, including: shared recognition of the importance of respectful, constructive and non-dogmatic exchange across an interdisciplinary range of heterodox and critical positions; overlapping concerns with the potential of empirically engaged and “substantivist” investigation (to borrow the Polanyian terminology), not just in testing and tweaking extant theories but in the construction of new insights, understandings and socio-political visions; and mutual commitments to humane, emancipatory and sustainable modes of socio-economic and ecological development.
Keywords: Karl Polanyi Institute of Political Economy; economic geography; markets

Economics as Social Science: Economics imperialism and the challenge of interdisciplinarity - Marchionatti, Roberto; Cedrini, Mario (Taylor & Francis, 2016)
There is a growing consensus in social sciences that there is a need for interdisciplinary research on the complexity of human behavior. At an age of crisis for both the economy and economic theory, economics is called upon to fruitfully cooperate with contiguous social disciplines. The term ‘economics imperialism’ refers to the expansion of economics to territories that lie outside the traditional domain of the discipline. Its critics argue that in starting with the assumption of maximizing behaviour, economics excludes the nuances of rival disciplines and has problems in interpreting real-world phenomena. This book focuses on a territory that persists to be largely intractable using the postulates of economics: that of primitive societies. In retracing the origins of economics imperialism back to the birth of the discipline, this volume argues that it offers a reductionist interpretation that is poor in interpretative power. By engaging with the neglected traditions of sociological and anthropological studies, the analysis offers suggestions for a more democratic cooperation between the social sciences. Economics as Social Science is of great interest to those who study history of economic thought, political economy and the history of economic anthropology, as well as history of social sciences and economic methodology.
Keywords: economic theory; economics imperialism